Experimental Studies on the Homogeneity and Compressive Strength Prediction of Recycled Aggregate Concrete (RAC) Using Ultrasonic Pulse Velocity (UPV) - Handika, Nuraziz; Norita, Balqis Fara; Tjahjono, Elly; Arijoeni, Essy (UI Scholars Hub, 2020)
The reuse of material from collapsed building debris as a natural aggregate substituent has been an alternative to solve concrete waste in Indonesia. However, its use in larger structures needs further research. The objectives of this research are to study the concrete homogeneity at a certain sample height and to find the strength prediction of Recycled Aggregate Concrete (RAC). In the previous laboratory study, the obtained concrete compressive strength with 20% RAC substitution (from the concrete ruins with fc’ = 30 MPa) was 27-30 MPa. Since, RAC contains natural aggregates and mixed cement paste, it is important to research the distribution, homogeneity and strength prediction of the concrete. The measurement was done using a non-destructive instrument called Ultrasonic Pulse Velocity (UPV). This paper presents a series of experiments investigating homogeneity and predicting compressive strength using both Destructive and Non-Destructive Tests (NDT). To do so, three steps in the experimental works were done. Firstly, UPV propagation measurements at four different levels through vertical prismatic beam specimens was performed. Two transducers were used in the direct mode of transmission with a 15 cm distance of measurement. Secondly, identical concrete samples cast in cubic form were measured using UPV and tested under compression. Thirdly, the core-drilled samples were taken from the vertical prismatic beam specimens for further investigation. The wave propagation velocity through RAC and the concrete compressive strength relationship demonstrate similar pattern as concrete with GFC (Gypsum-free-cement) performed by Brozovsky. This pulse velocity-concrete strength relationship can be used to predict the strength of RAC. Both the prediction curve and the homogeneity properties can be useful when casting a larger element of structures using RAC